Origin and diversification of major clades in parmelioid lichens (Parmeliaceae, Ascomycota) during the Paleogene inferred by Bayesian analysis. - Guillermo Amo de Paz; Paloma Cubas; Pradeep K Divakar; H Thorsten Lumbsch; Ana Crespo (PLoS ONE, 2011)
There is a long-standing debate on the extent of vicariance and long-distance dispersal events to explain the current distribution of organisms, especially in those with small diaspores potentially prone to long-distance dispersal. Age estimates of clades play a crucial role in evaluating the impact of these processes. The aim of this study is to understand the evolutionary history of the largest clade of macrolichens, the parmelioid lichens (Parmeliaceae, Lecanoromycetes, Ascomycota) by dating the origin of the group and its major lineages. They have a worldwide distribution with centers of distribution in the Neo- and Paleotropics, and semi-arid subtropical regions of the Southern Hemisphere. Phylogenetic analyses were performed using DNA sequences of nuLSU and mtSSU rDNA, and the protein-coding RPB1 gene. The three DNA regions had different evolutionary rates: RPB1 gave a rate two to four times higher than nuLSU and mtSSU. Divergence times of the major clades were estimated with partitioned BEAST analyses allowing different rates for each DNA region and using a relaxed clock model. Three calibrations points were used to date the tree: an inferred age at the stem of Lecanoromycetes, and two dated fossils: Parmelia in the parmelioid group, and Alectoria. Palaeoclimatic conditions and the palaeogeological area cladogram were compared to the dated phylogeny of parmelioid. The parmelioid group diversified around the K/T boundary, and the major clades diverged during the Eocene and Oligocene. The radiation of the genera occurred through globally changing climatic condition of the early Oligocene, Miocene and early Pliocene. The estimated divergence times are consistent with long-distance dispersal events being the major factor to explain the biogeographical distribution patterns of Southern Hemisphere parmelioids, especially for Africa-Australia disjunctions, because the sequential break-up of Gondwana started much earlier than the origin of these clades. However, our data cannot reject vicariance to explain South America-Australia disjunctions.